Development of teaching materials for trigonometric function graphs based on ICT and Tri-N for face-to-face and distance learning - Hera, Cicilia Jaga; Arcana, I Nyoman; Kusumaningrum, Betty; Sulaimon, Jamiu Temitope (Universitas Sarjanawiyata Tamansiswa, 2025)
The objectives of this research are to produce Tri-N and ICT-based teaching materials suitable for Face-to-Face Learning (FFL), create ICT and Tri-N-based teaching materials tailored for Distance Learning (DL), and evaluate the effectiveness and applicability of these materials across FFL and DL settings. The study contributes to academic discourse by demonstrating the efficacy of Tri-N and ICT-based teaching materials in enhancing mathematics instruction, particularly in the topic of Trigonometric Function Graphs. Using the ADDIE paradigm, which includes the phases of Analysis, Design, Development, Implementation, and Evaluation, the study employs the Research and Development (R&D) approach. The participants of the study consist of 36 Class X MIPA-2 students engaged in FFL and 36 Class X MIPA-1 students participating in DL at SMA Negeri 5 Yogyakarta. Learning outcomes evaluations, validation questionnaires, and answer questionnaires are some of the data collection techniques. To guarantee thorough review, the analysis combines qualitative and quantitative methodologies. The study's outcomes include the development of ICT and Tri-N-based teaching materials, such as learning videos, PowerPoint presentations, and handouts, with a primary focus on Trigonometric Function Graphs. These materials are made accessible through YouTube, with the link provided for broader dissemination. Expert assessments indicate high validity of the teaching materials, and student responses reflect positive reception and favorable average scores. The findings underscore the potential of these materials to enhance mathematics instruction in high school settings. It is recommended that educators integrate these resources into their teaching practices. Future research should investigate the application of ICT and Tri-N-based teaching materials across a broader range of subjects to further expand their impact on educational practices.